Was wir über Lernrückstände wissen (müssten)! - Kerstin Schneider (Wirtschaftsdienst, 2023)
– The effect of school closures and distance learning during the COVID19 pandemic on student achievement is still the subject of discussion. After the end of the pandemic-related restrictions, learning losses of students are being assessed and state programs were launched to help students catch up after Corona. However, to evaluate whether and how the programs have worked, reliable data on student achievement and a systematic monitoring of schools is needed. The paper argues that the data basis in Germany is not suf-ficient in an international comparison to fully assess the effects of the COVID19 pandemic on school students or to evaluate the govern-ment programs. This is a fundamental problem. The pandemic has only highlighted this once again.
Keywords: I21; I28; H52; 330; Schüler; Unterricht; Studierende; Lernen; Lernmethode; Epidemie; Deutschland; Schüler; Unterricht; Studierende; Lernen; Lernmethode; Epidemie; Deutschland